2021
DOI: 10.1186/s12931-021-01748-2
|View full text |Cite
|
Sign up to set email alerts
|

Acute exacerbation of fibrotic hypersensitivity pneumonitis: incidence and outcomes

Abstract: Background Patients with fibrotic hypersensitivity pneumonitis (HP) show variable clinical courses, and some experience rapid deterioration (RD), including acute exacerbation (AE). However, little is known about AE in fibrotic HP. Here, we retrospectively examined the incidence, risk factors, and outcomes of AE in fibrotic HP. Methods The incidence rates of AE were calculated in 101 patients with biopsy-proven HP. AE was defined as the worsening of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 36 publications
4
21
0
5
Order By: Relevance
“…Several studies have reported acute exacerbation (AE) in patients with fibrotic HP, following the same definition used in IPF, which results in poor prognosis ( 61 ). Recently it was reported as risk factors lower DLco, the presence of UIP-like pattern on HRCT at diagnosis, and cumulative incidence rates of AE showed high in-hospital mortality rate ( 62 ).…”
Section: Prognostic Factorsmentioning
confidence: 99%
“…Several studies have reported acute exacerbation (AE) in patients with fibrotic HP, following the same definition used in IPF, which results in poor prognosis ( 61 ). Recently it was reported as risk factors lower DLco, the presence of UIP-like pattern on HRCT at diagnosis, and cumulative incidence rates of AE showed high in-hospital mortality rate ( 62 ).…”
Section: Prognostic Factorsmentioning
confidence: 99%
“…Only a few studies have differentiated survival outcomes based on histologic subtype [ 107 ], with those having UIP-like findings and less cellularity and granuloma formation having poorer outcomes [ 71 ]. Lastly, acute exacerbation characterized by punctuated decline over several weeks with worsening clinical and radiologic findings has been reported in f-HP [ 111 ], occurring in up 18% over a median follow-up of 30 months with an in-hospital mortality of 44% in one series [ 112 ].…”
Section: Treatment Management and Prognosismentioning
confidence: 99%
“…Patients may also present with acute exacerbations (acute respiratory deterioration with new ground‐glass opacities on CT, not due to any other cause), with or without re‐exposure to the inciting antigen. Similar to other fibrotic ILDs, HP exacerbations are more common in those with a UIP‐like pattern and portend poor survival 64,65 …”
Section: Diagnosismentioning
confidence: 99%